COMPÓSITOS DO RESÍDUO DA Araucaria angustifolia COM POLIURETANA: UMA ABORDAGEM QUIMIOMÉTRICA - Stoski, Adriana (2014)
In this paper is about the chemical recycling of PET by catalytic glycolysis and later use of oligomers in the synthesis of a composite PU-Brazilian pine fruit was studied. For the glycolysis of PET a 22 factorial design was used, being evaluated the reaction temperature (150 and 170°C) and amount of water added in the reaction medium. The results showed that the two factors have significant influence on the depolymerization of PET, but the temperature in a higher intensity. There was also a physical chemistry study of the oligomers using the techniques FTIR, MEV, HPLC and titrations to obtain the medium molar mass. The HPLC technique showed that in 150 the molar masses of the oligomers are more uniform among the samples, while in 170°C they are more separate. In the experiments in which it was added 2% of water it was noticed the peak referring to TPA, possibly produced by BHET hydrolysis. It is also possible to realize that the samples of the first filtering material are less pure and have higher molar mass than the second filtering material, as showed by MEV. After the characterization, the sample 2FW was chosen for further studies, since it showed a good profit at the depolymerization of PET and there was also the formation of hydroxylated tetramers, being a better source of polyol to the formation of the a composite PU-Brazilian pine fruit. At this stage was also made a 2? factorial analysis, being evaluated reaction time and amount of scales, making clear that the analysis of the factors can`t be processed separately, since there is a strong interaction between the variables. It can be concluded that when it is added a bigger quantity of charge enforcement, the period of time for the reaction to modify the scales has to be high, being for 2h of reaction the quantity limit of the scale is 5% and for 4h, 15%. Through the mechanical analysis of the material, the sample 4 obtained the best final mechanical properties, at a value of 119,73, while the sample 3 obtained only a value of 17,90, the lowest value. Using the thermogravimetric techniques, it can be said that thermic stability of the composites is 245°C, when the degradation of the urethane ligation is started. It is also noticeable that the drying of the composites is more efficient in a N2 atmosphere for 48h and not in room temperature and atmosphere, as most works refer to. Finally, it can be certified that the techniques used in this work are efficient and the oligomers can be used as good chain extensors for polyurethane.